Using Shadowing Technique in Teaching English Pronunciation to Seventh Grade Students - Septyani Wulandari; Mukrim Mukrim; Hastini Hastini; Zarkiani Hasyim (Universitas Tadulako, 2023)
The objective of the study is to find out the effectiveness of the shadowing technique in teaching the English pronunciation to grade seven students of SMP Negeri 1 Mepanga in the academic year 2022/2023. The population of this pre-experimental research was grade seven students of SMP Negeri 1 Mepanga which consisted of 32 students of the VII B class chosen by using purposive sampling technique. The data were collected by using a pronunciation test conducted before and after the treatment, or pre-test and post-test. The data was analyzed by using simple statistics. The result shows that there was a significant improvement of the students’ pronunciation. It was proved by the result of the t-counted (16.67) which was greater than the t-table (1.696) in the significance degree, (0.05). The conclusion of this research indicated that the shadowing technique is effective and provides a significant effect to develop the student’s pronunciation. Keywords: Shadowing Technique, Teaching English Pronunciation.